I do not the question. Please explain
Answer:
x + 1
Step-by-step explanation:
3x - (2x + 4) + 5
3x - 2x - 4 + 5
x - 4 + 5
x + 1
Size bc it’s 8 numbers away
We are told that f(x) = x + 2. We want to find
.
Squaring f(x) on one side means we square x + 2 on the other.
So,
f(x) = x + 2
(f(x))² = (x + 2)²
= (x + 2)(x + 2)
We can use FOIL to square x + 2. The first terms multiply to x², the outside terms to 2x, the inside terms to 2x and the last terms to 4.
= x² + 2x + 2x + 4
= x² + 4x + 4
So [f(x)]² = x² + 4x + 4
D is the correct answer to your question